A rare case: Vesicoureteral reflux in Indonesian young adult with neurogenic bladder and chronic kidney disease stage 4. (February 2022) - Ardhany, Ardityo Rahmat; Suryantoro, Satriyo Dwi; Thaha, Mochammad; Santoso, Djoko
Abstract: Background: Vesicoureteral reflux (VUR) is one of the main causes of chronic kidney disease (CKD) in adolescence and young adult. It can be a congenital or an acquired anomaly and its uncommon in adult life. Case presentation: A 19th years old male with neurogenic bladder, VUR grade 4, CKD stage 4, malnutrition, and short stature. Radiological examinations show a spastic neurogenic bladder, cystitis, right VUR grade 4. Abdominal ultrasonography (USG) results were bilateral severe hydronephrosis due to post-renal causes. This patient had a history of myelocele excision at the age of 1.5 years. He had recurrent urinary tract infection with CKD stage 4. Discussion: The diagnosis of VUR and neurogenic bladder in CKD stage 4 is a rare case in nephrology. Conclusion: Indonesian male confirms of diagnosis VUR grade 4, neurogenic bladder, and CKD stage 4. Highlights: Vesicoureteral reflux (VUR) is one of the main causes of chronic kidney disease (CKD). VUR and neurogenic bladder are rare cases. The first report is on cases of VUR, neurogenic bladder, and CKD in Indonesia.